China’s ‘New International Order’: The Shanghai Cooperation Organisation in Afghanistan and Syria - Seiwert, Eva (Europe-Asia Studies, 2024)
Ever since its establishment, the Shanghai Cooperation Organisation (SCO) has positioned itself as representative of a ‘new international order’ in contrast to the US-led ‘old order’. This article argues that analysing the SCO’s response to international crises as practical implementations of its ‘new international order’ offers crucial insights into China’s vision for international relations. To that end, it examines the organisation’s response to crises in Afghanistan and Syria, outlining what kind of order the SCO propagates and what this means when acted out. The findings are based on qualitative content analysis of PRC and SCO documents and semi-structured expert interviews.
CRIS-Team Scopus Importer:2024-01-12

CHINA’S SEARCH FOR PARTNERS WITH SHARED WORLDVIEWS: EXPANDING THE “SHANGHAI COOPERATION ORGANIZATION FAMILY” - Seiwert, Eva (Asian Affairs, 2023)
The Shanghai Cooperation Organization (SCO) was the first multilateral institution to be initiated by the People's Republic of China and is now the world's largest regional organization. This study investigates how the SCO has enlarged its ‘circle of friends’, which I understand as one of several ways that China attempts to spread its vision of international relations internationally. I focus on two major ways through which the SCO has increased this ‘circle’, namely membership expansion and cooperation with other regional and international organizations. Drawing on official SCO and Chinese government documents as well as first-hand interview data gathered in China in 2018, the study offers insights into the core mechanisms through which the Chinese-led organization has expanded its ‘circle of friends’ and discusses these developments against the backdrop of China’s ambition to influence the international order through the SCO. The analysis will make evident that the SCO has managed to extend far beyond its founding member states and that this supposedly helps China gain support for its normative views and arguments on the international level.
CRIS-Team Scopus Importer:2023-10-20

From Academic Partner to 'Academic Threat': German and UK Media Framing of European-Chinese Academic Cooperation since Xi Jinping Came to Power - Seiwert, Eva (Bristol University Press, 2025)
CRIS-Team Scopus Importer:2025-05-30